HUBUNGAN SELF MANAGEMENT DENGAN KECANDUAN GAME ONLINE SISWA KELAS XI DI SMAN 1 PRAYA BARAT KABUPATEN LOMBOK TENGAH TAHUN PELAJARAN 2021/2022 - Khairul Dwi Cahya; I Made Sonny Gunawan; Jesicca Festy Maharani (Journal of Mandalika Literature, 2022)
Self-management is self-control of thoughts, words, and actions that are carried out, and encourage oneself to do things that are not good and increase good and right actions. Addiction Online Game is one of the problems that gets the attention of the wider community because this problem will have an impact on several aspects of life, such as health aspects, psychological aspects, academic aspects, social aspects and financial aspects. The aim of this research is to determine the relationship between self management with addiction online game in class XI students at SMAN 1 Praya Barat, Central Lombok Regency, in the 2021/2022 academic year. In this case the researcher will use quantitative research methods with the type of correlational research. In this study , the research population was 191 students and the sample used by this researcher was some students of SMAN 1 Praya Barat in class XI IPS with a total of 87 students. The sampling technique used in this research is purposive sampling. While the data collection techniques used are questionnaires, observations, interviews, and documentation.Correlation formula Product Moment, where the results of the t-count data analysis are 0.841 with a t-table value with db (N-1) = 87-1 = 86 with a significant level of 5% is 0.213. Thus, the t-count value is greater than the t value in the table (0.841 > 0.213), so it can be concluded that there is a relationship between self management with addiction online game in class XI students at SMAN 1 Praya Barat, Central Lombok Regency, in the 2021/2022 academic year. So the results of this study were declared "Significant".